Zhang Youkang liu Yu'ning yang shen yin shi : dazi ban = Kidney - Zhang Youkang, 1946-; Liu, Yuning (Beijing: China Light Industry Press, 2022)
This book tells readers why health care should first nourish the kidney, which nutrients help to nourish the kidney and protect the body, which should control the intake, what are the common foods that should be eaten to nourish the kidney, commonly used medicinal and dietary prescriptions for nourishing the kidney and benefiting the kidney, as well as the key points of kidney nourishment in different seasons and the diet maintenance program for common kidney diseases.
Text in simplified Chinese scripts
Keywords: Kidneys -- Diseases -- Diet therapy -- Recipes; Peritoneal dialysis -- Patients -- Nutrition; Cookbooks